2015
DOI: 10.5935/abc.20150045
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Function in Patients with Chronic Chagasic Cardiomyopathy

Abstract: BackgroundChagas disease is a cause of dilated cardiomyopathy, and information about left atrial (LA) function in this disease still lacks.ObjectiveTo assess the different LA functions (reservoir, conduit and pump functions) and their correlation with the echocardiographic parameters of left ventricular (LV) systolic and diastolic functions.Methods10 control subjects (CG), and patients with Chagas disease as follows: 26 with the indeterminate form (GI); 30 with ECG alterations (GII); and 19 with LV dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Diastolic dysfunction contributes to left atrium (LA) remodeling and dysfunction, particularly in patients with LV dysfunction [8,36,49]. Measurement of LA volume (LAV) and indexing it to body surface area (LAVi) has been demonstrated to be a marker of duration and severity of diastolic dysfunction.…”
Section: Left Atriummentioning
confidence: 99%
See 1 more Smart Citation
“…Diastolic dysfunction contributes to left atrium (LA) remodeling and dysfunction, particularly in patients with LV dysfunction [8,36,49]. Measurement of LA volume (LAV) and indexing it to body surface area (LAVi) has been demonstrated to be a marker of duration and severity of diastolic dysfunction.…”
Section: Left Atriummentioning
confidence: 99%
“…It is also useful in Chagas disease patients to predict prognosis. Left atrium volume can be increased in all stages of ChD [36,49,50], and LA function seems to be more significantly compromised in ChD than in idiopathic cardiomyopathy [51], suggesting a component of atrial myopathy. However, a study using strain to analyze atrial function demonstrated impairment to a degree similar to that of idiopathic dilated cardiomyopathy [52].…”
Section: Left Atriummentioning
confidence: 99%
“…O comprometimento das funções de reservatório, conduto e bomba do átrio esquerdo foram frequentes em pacientes com miocardiopatia chagásica e disfunção sistólica de VE. Enquanto os pacientes com função sistólica normal não tiveram alterações dos parâmetros de átrio esquerdo (FRAGATA et al, 2015) Quando comparado ao gênero evidenciou o que o sexo masculino possui acometimento maior da fibrose miocárdica e pior remodelamento ventricular ao método de ressonância magnética. Esta ainda evidenciou maior sensibilidade em relação a ecocardiografia na avaliação da fração de ejeção do ventrículo direito.…”
Section: Brazilian Journal Of Developmentunclassified
“… 13 , 14 In our experience, creatinine, in these cases, usually falls at the end of hospitalization or about 30 days after discharge. 14 , 15 In other words, elevated creatinine at admission appears to be a reflection of congestion of the renal veins and transient increases are a consequence of the volume reduction process. Congestion, regardless of worsening of renal function, is associated with worse prognosis.…”
Section: Hypotension Bradycardia and Renal Dysfunction As Obstacles mentioning
confidence: 99%